Intervención del terapista respiratorio en paciente femenino de 73 años de edad con diagnóstico de neumonía bacteriana adquirida en la comunidad. - Miranda Garcia, Diana Gabriela (2022)
The focus of this study is based on the intervention of the respiratory therapist in a 73-year-old female patient diagnosed with community-acquired bacterial pneumonia. Community-acquired bacterial pneumonia is one of the main lung diseases affecting older adults and children around the world. This pathology is mainly caused by the bacteria Streptococcus pneumoniae. Bacterial pneumonia acquired in the community in our country in the last 5 years is considered a serious health problem because it is among the 3 leading causes of morbidity in pediatric patients and in the elderly, being one of the main reasons for consultation and hospital admissions in the different hospitals of the country. The main factors causing bacterial pneumonia acquired in the community in the 73-year-old female patient are cigarette smoke since the patient lives with a relative who is an active smoker, in addition to the fact that the patient is immunosuppressed due to her age and that he suffers from type 2 diabetes mellitus and arterial hypertension and all of these are one of the main risk factors for the development of said respiratory pathology.